1994
DOI: 10.1136/adc.70.6.476
|View full text |Cite
|
Sign up to set email alerts
|

Intellectual, educational, and behavioural sequelae after cranial irradiation and chemotherapy.

Abstract: Cognitive and educational sequelae are inconsistently reported in children treated with cranial irradiation for acute lymphoblastic leukaemia. This study investigated differences in these skills after cranial irradiation, controlling the effects of chemotherapy and psychosocial factors. Three groups were evaluated: 100 children diagnosed with acute lymphoblastic leukaemia and treated with cranial irradiation and chemotherapy; 50 children diagnosed with acute lymphoblastic leukaemia or other cancers and treated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
65
5
3

Year Published

1996
1996
2012
2012

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 113 publications
(82 citation statements)
references
References 42 publications
9
65
5
3
Order By: Relevance
“…CRT is associated with poor educational outcomes among survivors of childhood cancer, 24,27,28 as we also demonstrated in the current study. Reports have indicated that IT MTX is a risk factor for poor cognitive performance and neurologic function.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…CRT is associated with poor educational outcomes among survivors of childhood cancer, 24,27,28 as we also demonstrated in the current study. Reports have indicated that IT MTX is a risk factor for poor cognitive performance and neurologic function.…”
Section: Discussionsupporting
confidence: 63%
“…Younger age at diagnosis and/or treatment 7,14,[24][25][26] ; cranial or craniospinal radiotherapy (CRT) and/or intrathecal methotrexate (IT MTX) 15,24,25,[27][28][29] ; higher therapeutic doses of CRT or IT MTX 17,24 ; and diagnoses of central nervous system (CNS) tumors, leukemia (particularly acute lymphoblastic leukemia [ALL]), Hodgkin lymphoma, or neuroblastoma 13,15,30 as well as being female, [30][31][32][33] of lower socioeconomic status (SES), 20 and having a longer time since diagnosis 24 have been reported to be associated with an increased risk of poorer educational outcomes. Previous studies have not always assessed the potential confounding effects of missed school, 34 SES, 35 and physical health or physical impairments.…”
mentioning
confidence: 99%
“…Previous research has also suggested that educational difficulties may be a result of missed schooling (Eiser, 1980;Sawyer et al, 1989) but the observation that children in group 2, who also missed significant school time, are performing similarly to healthy controls argues against this explanation. Thus we have shown that the problem is related to treatment rather than psychosocial factors (Anderson et al, 1994). Dose of irradiation A number of previous studies have addressed the impact of high-or low-dose CRT, with little consensus with respect to findings (Trautman et al, 1988;Schuler et al, 1981;Appleton et al, 1990;Mulhern et al, 1992;Halberg et al, 1992;Hirsch et al, 1979).…”
Section: Discussionmentioning
confidence: 77%
“…There was no correlation between the presence of neurological signs and intellectual or educational deficits. The results have been published and discussed in detail (Anderson et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, in survivors of medulloblastoma, a deficit in academic achievement, memory, attention, and processing speed has been evidenced [5, 9, 10, 13, 15-17, 19, 21] . Combined radio-and chemotherapy reduced cognitive performances and was associated with memory loss, concentration, and learning problems [5,[13][14][15][16]18] . The most commonly affected neurocognitive functions were loss of attention and concentration [9,10,19,21] , and memory problems [5,13,19] , in particular working memory [10,22] ; also the visuo-motor integration and visuo-spatial abilities [5,9,20,21,[23][24][25] , executive and verbal functions [13,14,20] , speed of execution [13,20] , and problem-solving abilities were affected [20] .…”
Section: Late Neurocognitive Effects On Personal Areasmentioning
confidence: 99%